The great fossil enigma : the search for the conodont animal - Knell, Simon J. (Life of the past., 2012)
Stephen Jay Gould borrowed from Winston Churchill when he described the conodont animal as a ""riddle wrapped in a mystery inside an enigma."" This animal confounded science for more than a century. Some thought it a slug, others a fish, a worm, a plant, even a primitive ancestor of ourselves. The list of possibilities grew and yet an answer to the riddle never seemed any nearer. Would the animal that left behind these miniscule fossils known as conodonts ever be identified? Three times the animal was ""found, "" but each was quite a different animal. Were any of them really the one? Simon J.